ENFORCEMENT OF THE MAINTENANCE RIGHTS OF A SPOUSE, MARRIED IN TERMS OF ISLAMIC LAW, IN THE SOUTH AFRICAN COURTS - Marita Carnelley (Obiter, 2022)
The purpose of this discussion is to note the application of the maintenance statutes vis-à-vis Muslim couples in the South African courts. Firstly, the important judgments are referred to in chronological order; secondly, the maintenance rights of a Muslim spouse are set out for the following periods: during the marriage, after death of her husband and postdivorce; and lastly, the jurisdiction of the courts are discussed in light of the changing mores of society. In short, the question is how far the South African courts have gone in making the South African legal maintenance legislation accessible to Muslim wives. The issues are discussed in light of the Islamic family law as interpreted by the South African courts and with reference to the draft bill.